The psychological impact of Covid-19 on front line nurses: a synthesis of qualitative evidence - Gonzalez, Sara Huerta (2021)
Caring for people with COVID-19 on the front line has psychological impacts for healthcare professionals. Despite the important psychological impacts of the pandemic on nurses, the qualitative evidence on this topic has not been synthesized. Our objective: To analyze and synthesize qualitative studies that investigate the perceptions of nurses about the psychological impacts of treating hospitalized people with COVID-19 on the front line. A systematic review of qualitative studies published in English or Spanish up to March 2021 was carried out in the following databases: The Cochrane Library, Medline (Pubmed), PsycINFO, Web of Science (WOS), Scopus, and CINHAL. The PRISMA statement and the Cochrane recommendations for qualitative evidence synthesis were followed. Results: The main psychological impacts of caring for people with COVID-19 perceived by nurses working on the front line were fear, anxiety, stress, social isolation, depressive symptoms, uncertainty, and frustration. The fear of infecting family members or being infected was the main repercussion perceived by the nurses. Other negative impacts that this review added and that nurses suffer as the COVID-19 pandemic progress were anger, obsessive thoughts, compulsivity, introversion, apprehension, impotence, alteration of space-time perception, somatization, and feeling of betrayal. Resilience was a coping tool used by nurses. Conclusions: Front line care for people with COVID-19 causes fear, anxiety, stress, social isolation, depressive symptoms, uncertainty, frustration, anger, obsessive thoughts, compulsivity, introversion, apprehension, impotence, alteration of space-time perception, somatization, and feeling of betrayal in nurses. It is necessary to provide front line nurses with the necessary support to reduce the psychological impact derived from caring for people with COVID-19, improve training programs for future pandemics, and analyze the long-term impacts.